Поповичу Мирославу Володимировичу – 75 років. Віхи наукової біографії - Йолон, П.Ф. (Інститут держави і права ім. В.М. Корецького НАН України, 2005)
В статье излагаются творческий путь и достижения в науке юбиляра Мирослава Владимировича Поповича. Юбиляр – известный современный украинский философ, директор Института философии им. Г. С. Сковороды Национальной академии наук Украины, один из редакторов-основателей международного журнала “Проблемы философии права”. The article sets out the scientific path and work of Myroslav Volodymyrovych Popovych who celebrates
his 75th anniversary. The honored is a prominent contemporary Ukrainian academic philosopher,
the Director of the H. S. Skovoroda Institute of Philosophy of the National Academy of Sciences of
Ukraine, one of the coeditors-in-chief and cofounders of the International Journal “Philosophy of Law
Issues”.